The Effect of Feed Quality on the Development and Function of Immune System in Chicken - Nnadi, P.A.; Ezema, K.C. (International Journal of Poultry Science, 2010)
A total of 72 day old cockerel Harco chicks purchased from a local hatchery were used to investigate the effect of feed quality on the development and function of immune system in chicken. Upon procurement, they were divided into 3 equal groups (n = 24) and brooded separately in three mini deep litter brooder pens with adequate brooding requirement Three diets with crude protein contents of 26, 22 and 17% were prepared and from day zero of hatch till day 26, chicks in group A were fed 26 while groups B and C were fed 22 and 17% respectively. During and after brooding, signs of ill health such as diarrhoea, anorexia, huddling, drooping of wings, coughing and mortality were carefully monitored. Post brooding, each group retained its pen but all the groups were maintained on one diet, lpd on which they were fed till the end of the study. On day 21 Post Hatch (PH), 8 chicks per group were randomly selected, weighed individually and their group means and standard deviation calculated. They were subsequently sacrificed and through jugular venipunture, 2 ml of blood was collected into an anticoagulant bottle for general haematology while 5 mls was collected into a non anticoagulant containing bottle for serum biochemistry and serology. This was followed by necropsy of all the chicks after which some lymphoid organs and the liver were harvested and their weights determined followed by that of their relative weights. The remaining birds in each group were vaccinated with ND vaccine lasotaR. Five days later, all the operations of day 21 were repeated. The remaining chicks in the group were hereafter maintained on 17% CP till day 42 PH when they were vaccinated with ND KomarovR vaccine. Five days later, all the operations of day 21 were repeated. We observed the loss of 17% of the flock population in group A during brooding. On days 21, 26 and 47 PH groups A and B had comparable mean live weights which were significantly higher than the mean weights of group C (p<0.05). Also, all the groups had comparable mean relative organ weights throughout the period of study. Moreover, on days 21 and 26 PH, all the groups had comparable PCV while on day 47, groups A and B had mean values significantly higher than C (p<0.05). Generally, we observed that dietary protein appears to modulate the rate of growth and function of some lymphoid organs in growing chicks.